Economic and Social Influences of The Equestrian Sector Development in Romania - Oana Daniela LUPOAE; Andrei-Mirel FLOREA; Riana Iren RADU; Dumitrache Bogdan BRATOVEANU; Silvius STANCIU (Communications of International Proceedings, 2020)
The equestrian sector has an important role in protecting the environment, social welfare and economic growth. Currently this sector is in the development stage both internationally and nationally. The horse remains on a competitive market regardless of the form of tourism, management or marketing, because it respects the natural, social and economic integrity of the environment, ensuring the exploitation of natural and cultural resources for future generations. Sustainable tourism development is not just a concept when it comes to horses but it is a starting point for meeting the needs of the tourists and of the local population. In Romania, equestrian sports are not as developed as in other states, whether they are sports events or recreational activities. The aim of the study is to provide a broader perspective for the future management of the equestrian industry, as well as for the development capacity of this market.
Keywords: Equestrian sports; economy; tourism; management; sustainable development.